A C-Band Compact High Power Active Integrated Phased Array Transmitter Module Using GaN Technology - Gholami, Mehrdad (Université d'Ottawa / University of Ottawa, 2017)
In this research, an innovative phased array antenna module is proposed to implement a high-power, high-efficient and compact C-band radio transmitter. The module configuration, which can be integrated into front-end circuits, was designed as planar layers stacked up together to form a metallic cube. The layers were fabricated by using a Computer Numerical Control (CNC) milling machine and screwed together. The antenna parts and the amplifier units were designed at two opposite sides of the cube to spread the dissipated heat produced by the amplifiers and act as a heat sink. Merging the antenna parts with the amplifier circuits offers additional advantages such as decreasing the total power loss, mass, and volume of the transmitter modules by removing the extra power divider and combiner networks and connectors between them as well as reducing the total signal path. To achieve both a maximum possible radiation efficiency and high directivity, the aperture waveguide antenna was selected as the array element. Four antenna elements have been located in a cavity to be excited equally and the cavity is excited through a slot on its underside so a compact subarray is formed. Antenna measurements demonstrated a 15.5 dBi gain and 20 dB return loss at 10 % fractional bandwidth centered around 5.8 GHz and with more than 98% radiation efficiency. The total dimensions of the subarray are approximately 8*12*4 cm3. The outcoming signal from the amplifiers is transferred into the slot exciting the subarray through a microstrip-to-waveguide transition (MWT). A novel and robust MWT structure was designed for the presented application. The MWT was also integrated with a microstrip coupler to monitor the power from the amplifier output. The measured insertion loss of the MWT along with the microstrip coupler was less than 0.25 dB along with more than 20 dB return loss within the same bandwidth of the subarray. The microstrip coupler shows 38 dB of coupling and more than 48 dB of isolation with negligible effects on the amplifier output signal and the insertion/return loss of the MWT. The amplifier subcomponents consist of power combiners/dividers (PCDs), high power amplifiers (HPAs) and bias circuitry. A Monolithic Microwave Integrated Circuit (MMIC) three-stage HPA was designed in a commercially available 0.15 um AlGaN/GaN HEMT technology provided by National Research Council Canada (NRC) and occupies an area of 4.7*3.7 mm2. To stabilize the HPA, a novel inductive degeneration technique was successfully used. To the best of the author’s knowledge, this is the first time this technique has been used to stabilize HPAs. Careful considerations on input/output impedances of all HEMTs were taken into account to prevent parametric oscillations. Other instability sources, i.e. odd-mode, even-mode, and low frequency (bias circuit) oscillations were also prevented by designing the required stabilization circuits. The electromagnetic simulation of the HPA shows 35 W (45.5 dBm) of saturated output power, 26 dB large signal gain and 29% power added efficiency within the same operating bandwidth as the subarray. The output distortion is less than 27 dB, indicating that the HPA is highly linear. The PCD was designed by utilizing a novel, enhanced configuration of a Gysel structure implemented on Rogers RT-Duroid5880. The insertion loss of the Gysel is less than 0.2 dB while return loss and isolation are greater than 20 dB over the entire bandwidth. The same subarray area (8*12 cm2) has been used for the amplifier circuits and up to eight HPAs can be included in each module. All the above parts of the transmitter module were fabricated and measured, except the MMIC-HPA.
Keywords: High power amplifier; Antenna; Transmitter; MMIC